Governance infrastructure and location of foreign direct investment in the people's Republic of China - Jia He; Oliver M. Rui; Xiaolei Zha (Asian Development Bank Institute (ADBI), 2011)
Standard neoclassical theory predicts that capital should flow from rich to poor countries. However, Lucas (1990) points out that these capital flows are actually very modest, and nowhere near the levels predicted by theory. The People's Republic of China (PRC) now receives more foreign capital in the form of foreign direct investment (FDI) than any other country, but statistics indicate that this inward FDI flows unequally to different regions. In this study, using hand-collected data on FDI for more than 200 cities, we examine whether the Lucas paradox of capital exists within the PRC. We adopt the dynamic panel data generalized method of moments (GMM) framework to avoid the potential endogeneity issue. Using both provincial- and city-level data, the empirical results show that FDI flows to the PRC, as proxied by total gross domestic product (GDP) and per capita GDP, favor rich regions over poor regions. We also find that regional economic growth has no significant impact on FDI. These findings support the existence of the Lucas paradox in the PRC. We demonstrate that this paradox is not driven by government policy and explore possible explanations for its existence.
Keywords: F21; 330; Direktinvestition; Räumliche Verteilung; Neue klassische Makroökonomik; Momentenmethode; Schätzung; China